PEDAGOGICAL CONTENT OF PREPARING PRIMARY CLASS STUDENTS FOR CREATIVE ACTIVITY (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In this article, the pedagogical content of the teacher's tasks, which should be used in order to develop creative abilities of primary school students, is presented.